Cognitive Skills and Youth Labor Market Outcomes - Lee, Jean N.; Newhouse, David (World Bank, Washington, DC, 2013)
This paper provides new cross-country evidence on the impact of cognitive skills, as measured by international achievement tests, on subsequent youth employment outcomes. In our initial analysis, we find that high average scores are strongly associated with increases in school enrollment and large reductions in the incidence of unemployment, with slightly stronger effects for women. Higher scores also correlate with a larger share of youth employed in wage and salaried jobs, outside of agriculture, and to some extent in higher status occupations, but these findings are less robust. Conditional on average test scores, greater within-cohort dispersion lead to reduced school attendance and increased employment at young ages, perhaps reflecting the less precise signal value of further formal educational attainment in the presence of large quality differences. In specifications including both educational attainment and measured test scores, test scores have stronger effects on unemployment, but attainment is also strongly predictive of employment and some measures of job quality. We conclude that while increasing education quality can play a central role in improving youth employment outcomes, increasing attainment remains an important and complementary objective to foster the creation of better jobs for youth. However, preliminary extensions to the existing analysis using data from additional countries and years suggest much more important effects of test scores on measures of job quality, such as wage and non-agricultural employment, than on employment, enrollment, unemployment, or labor force participation.